PERGESERAN PERAN DAN FUNGSI ALUN-ALUN KALIWUNGU SEBAGAI RUANG TERBUKA PUBLIK - Indrianingrum, Lulut; Azizah, Anis Nur; Prasetya, Gilang Eko; Hidayah, Nurul (Semarang State University, 2015)
The existence of the square Kaliwungu very far from the characteristics of such a square. Not only the shape, but the function of the square has also shifted away. Although the existence as public space Â was still visible in the morning, but it the afternoon until evening, the square transformed into market. The function of the square as a public open space has been dominated as economic functions. From time to time the role of the square undergone many changes since the days of pre-colonial, colonial, post-colonial and current period. Changes in the role and function of the square as a public open space Kaliwungu basically occurs when the policy was issued regarding the transfer function around the market square into the parking lot of the mosque. It shows that the square as the center of the city has a strategic location that can not be separated from economic activities.Keberadaan alun-alun Kaliwungu sangat jauh dari karakteristik sebuah alun-alun tersebut. Tidak hanya bentuknya, tapi fungsi alun-alun juga sudah bergeser jauh. Walaupun pada pagi hari masih nampak keberadaannya, namun coba kita lihat pada sore hingga malam hari, alun-alun Kaliwungu berubah total menjadi pasar sore kaliwungu. Fungsi alun-alun sebagai ruang terbuka publik telah terdominasi sebagai fungsi ekonomi. Dari waktu ke waktu peran alun-alun mengalami banyak perubahan sejak zaman pra kolonial, kolonial, pasca kolonial dan masa saat ini. Perubahan peran dan fungsi alun-alun Kaliwungu sebagai ruang terbuka publik yang paling mendasar terjadi saat dikeluarkan kebijakan mengenai pengalihan fungsi pasar disekitar alun-alun menjadi tempat parkir masjid. Hal tersebut menunjukan bahwa alun-alun sebagai pusat kota memiliki letak strategis yang tidak dapat dipisahkan dengan kegiatan ekonomis.